International crisis management : the approach of European states - Houben, Marc, 1967- (Routledge studies in governance and change in the global era, 2005)
Over the past fifty years, crisis management has become essential to achieving and maintaining national security. This book offers a comparative analysis of the preconditions and constraints nine European states place on their participation in international crisis management operations and the important consequences of such decisions, and provides a theoretical framework to help the reader understand this complex decision-making process.